Proyecto de inversión para la construcción de residencia para estudiantes politécnicos de provincia en la ciudad de Guayaquil - Lucas Cedeño, Ronald (2009)
Nowadays there are a high percentage of diseases such as typhoid, cholera, etc, produced by lack of hygiene in restaurant kitchens. This problem occurs because of a bad use of detergent to clean them. For this reason we decided to design a specialized product for the cleaning of industrial kitchens which is focus for those restaurants that are found with the need to provide a service and meals with an excellent hygienic preparation. Thinking not just of the population but also in that restaurant’s owners can buy a product that ensures effective in removing food debris, and also runs the risk of bacteria, the formula that we provide in our product proves effective through its agents, penetrating solvents that facilitate removal of heavy grease and burnt residue that accumulate on the inside and outside of the kitchen leaving the alkali compounds act to solubilize grease and dirt, this product will be marketed by the name of CLEAN SI.